Cognition, knowledge and social action in the multiplicity paradigm - Mazur, Stanisław (Journal of Public Governance, 2013)
The paper is an attempt to explain how the subjectivity of perceptions of the social world is generated, and clarifies some issues related to the reconciliation of its multiple reflections. The author describes the rules and mechanisms inherent in the process through which subjectivity is transformed into social objectivity. This is effected by exploring the paradigm of the multitude and its two traditions – differentiating and consolidating ones. The paper concludes with a description of the basic findings resulting from the analysis of this paradigm as well as a discussion of its advantages, limitations and its relation to the positivist paradigm.